Corporate finance and restructuring: evidence from Central and Eastern Europe - Jens Köke; Tanja Salem (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
After the end of communism enterprises in Central and Eastern Europe (CEE) were marked by low levels of labor productivity, mainly because of too high employment levels. According to economic theory, the corporate capital structure can be an important element in the restructuring process. But both, empirical evidence on corporate finance in CEE countries and its relation to employment is still sparse. This study describes the patterns of the corporate capital structure for ten CEE countries over the years 1993-1998, taking two major Western economies as a benchmark. An impressive rise in total indebtedness suggests that there is room for creditors to fulfill their role in corporate governance. On the other hand, investment is predominantly financed internally in CEE firms, making creditor and shareholder governance more difficult. But a regression analysis shows that inefficient CEE firms are forced to downsize employment when they finance themselves largely externally, but less so for those firms with high levels of debt. However, downsizing is limited by soft budget constraints.
Keywords: O12; G31; G34; 330; Central and Eastern Europe; corporate finance; industry restructuring; Kapitalstruktur; Reorganisation; Budgetrestriktion; Corporate Governance; Schätzung; Osteuropa; Downsizing